Evidence map of nutrient interventions for major depression: a systematic review protocol - Dongbo Zhang; Chenqi Li; Xue Tian; Gen Miao; Wenjing Shi; Hongtao Lu; Yicui Qu; Mengyu Cai; Yuxiao Tang; Hui Shen; Biao Gao (Systematic Reviews)
Abstract Background Depression severely impacts quality of life globally. While traditional treatments show efficacy, many patients respond poorly. Nutritional interventions demonstrate potential as safe, economical adjunctive therapies. However, current evidence is scattered and heterogeneous, lacking systematic evaluation. This study aims to systematically evaluate evidence for various nutritional interventions in depression and create an evidence gap map (EGM). Methods We will conduct a systematic review using the EGM approach. Major medical databases will be searched for relevant studies published up to present. Two independent researchers will screen literature, extract data, and assess evidence quality. Multiple tools will be used for quality assessment: Cochrane Risk of Bias Tool 2.0 for RCTs, ROBINS-I for non-RCTs, Newcastle–Ottawa Scale for observational studies. The GRADE system will be employed for overall evidence grading. EPPI-Reviewer Web will generate the EGM. We will analyze evidence distribution, time trends, and explore impacts of population characteristics and depression subtypes. Discussion This study will provide critical methodological references for nutritional psychiatry. Expected results include identifying nutrient categories with robust antidepressant evidence, evaluating evidence distribution for different interventions, and exploring differential effects across populations and depression subtypes. Findings will inform individualized nutritional strategies, improve clinical guidelines, and potentially influence public health policies. Systematic review registration CRD42024590644. Date of registration: 30/09/2024.